The effect of PBL integrated RMS on biological literacy and critical thinking ability of high school students - Khairotun Nihlah; Rizhal Hendi Ristanto; Tri Handayani Kurniati (University of Muhammadiyah Malang, 2024)
This study aimed to determine the effect of Problem-Based Learning (PBL) integrated Reading, Mind Mapping, and Sharing (RMS) on biological literacy and critical thinking skills in biotechnology material. This type of research is Quasi-Experimental with pre-test-post-test experiments and a control group design. The researcher conducted the research because most of the students who became respondents considered biotechnology material less attractive, so students' understanding and activeness could have been more optimal in the learning process. The research samples were 72 students of class X MIPA at SMA Negeri 2 Kota Serang, Banten. The research sample was divided into two groups: the experimental group that applied the PBL integrated RMS model and the control group that applied the PBL model. The research instruments used were biological literacy ability tests and critical thinking ability tests. Biological literacy skills were measured using biological literacy-based multiple-choice test instruments, while critical thinking skills were measured using essay test instruments. The hypothesis test used was MANOVA statistical analysis. The results of statistical tests showed a significant effect of PBL integrated with RMS on biological literacy and critical thinking skills on biotechnology material with a significance value of 0.000 < α. Students with an integrated RMS learning model are more effective than those with a PBL learning model, which is indicated by the post-test value being higher than the pre-test value. This research contributes to the field of biology education by showing that the PBL learning model integrated with RMS can be an effective alternative learning model to improve students' biological literacy and critical thinking skills. The findings of this study are expected to be useful for biology teachers